1987
DOI: 10.1128/iai.55.5.1207-1215.1987
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity in Haemophilus pleuropneumoniae

Abstract: Genetic diversity among 135 isolates of nine serotypes of Haemophilus pleuropneumoniae recovered from pigs with pleuropneumonia or other invasive diseases in 14 countries was estimated by multilocus enzyme electrophoresis, which detects allelic variation in structural genes. Thirty-two multilocus genotypes (electrophoretic types [ETs]) were distinguished on the basis of allele profiles at 15 enzyme loci, and 36 distinctive combinations of ET and serotype were identified. The recovery of isolates with identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
2

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 24 publications
3
21
2
Order By: Relevance
“…In agreement with previous findings (10, 17,21) this study revealed that the species A. pleuropneumoniae has a clonal structure. Of 250 isolates analyzed, 66% belonged to three ETs (ET-10, ET-15, and ET-17) of a total of 37 ETs identified in the study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous findings (10, 17,21) this study revealed that the species A. pleuropneumoniae has a clonal structure. Of 250 isolates analyzed, 66% belonged to three ETs (ET-10, ET-15, and ET-17) of a total of 37 ETs identified in the study.…”
Section: Discussionsupporting
confidence: 93%
“…As seen in Table 2, the genetic diversity (H) of the serotypes differed significantly among the 187 Danish isolates. As the calculated genetic diversity will depend, in part, on the selection of isolates, enzymes, and running conditions chosen for MEE, it is difficult to form any conclusions about the H values in our work compared with those reported by Musser et al (17). However, in general, the genetic variance of the total number of isolates is smaller in our work (0.247 compared with 0.428).…”
Section: Discussioncontrasting
confidence: 66%
“…Thus, intramuscular injection of a bacterin prepared from one serotype protects from homologous but not heterologous challenge (14). This antigenic variability among A. pleuropneumoniae serotypes has been confirmed by comparison of the outer membrane profiles and by multilocus enzyme electrophoresis indicating a clonal origin of isolates belonging to the same serotype (21).…”
mentioning
confidence: 60%
“…In fact, the serotype 7 FhuA protein showed a higher level of homology to FhuA of E. coli than to that of A. pleuropneumoniae serotype 1. Such discrepancies be- tween proteins belonging to strains from di¡erent serotypes support the clonal population structure of A. pleuropneumoniae [23]. To date, two other serotype-speci¢c outer membrane proteins of A. pleuropneumoniae have been identi¢ed, the outer membrane lipoprotein OmlA [24] and the transferrin-binding protein TbpB [14].…”
Section: Discussionmentioning
confidence: 95%